2020
DOI: 10.21203/rs.2.22773/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The predictive value of lncRNA MIR31HG expression on clinical outcomes in patients with solid malignant tumors

Abstract: Background Emerging studies have explored the prognostic value of MIR31HG in cancers, but its role remains elusive. Herein, we aimed to summarize the prognostic potential of MIR31HG in this study. Methods Several databases were searched for literature retrieval on Dec 5, 2019. Overall and subgroup analyses were conducted to measure the relationship between MIR31HG expression and clinical outcomes. Moreover, GEPIA was applied for validation of prognostic value of MIR31HG in tumor patients in TCGA dataset. Resul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Cancer is one of the life‐threatening diseases and remains a critical public health issue worldwide 1‐3 . Despite the tremendous improvements in cancer therapy in recent decades, there are still many patients who suffer from unsatisfactory outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is one of the life‐threatening diseases and remains a critical public health issue worldwide 1‐3 . Despite the tremendous improvements in cancer therapy in recent decades, there are still many patients who suffer from unsatisfactory outcomes 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Compelling experimental evidences indicate an engagement of lncRNAs in pleiotropic pathophysiological functions related to tumorigenesis, like the cell growth, invasion, metastasis, apoptosis and chemo‐resistance, 16 by interaction with other macromolecules 17 . Accumulating studies have shown that lncRNAs could be considered as a promising candidate in cancer prognosis and diagnosis 1,4,7,18 . Accordingly, lncRNAs have attracted great attention due to their multifaceted modulatory functions and the capacity as predictive biomarkers in cancers 1,4,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long non-coding RNAs (lncRNAs) belong to non-coding RNAs whose lengths are longer than 200bp [7]. They have little or no capability of coding protein [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that lncRNAs could drive pathophysiologic phenotypes through interaction with other cellular macromolecules including DNA, RNA and proteins [9]. Aberrant expression or functional abnormalities of LncRNAs have been linked with numerous human diseases, such as aging [10], degenerative disease [11], and cancer [12,7,13,14]. Recently, a pivotal role of lncRNA in tumor biological characteristics including proliferation, cell cycle arrest, invasion, migration [15], autophagy [16], and drug resistance [17] has also been revealed.…”
Section: Introductionmentioning
confidence: 99%